2002
DOI: 10.1536/jhj.43.367
|View full text |Cite
|
Sign up to set email alerts
|

Role of Signal-Averaged Electrocardiograms for Predicting the Inducibility of Ventricular Fibrillation in the Syndrome Consisting of Right Bundle Branch Block and ST Segment Elevation in Leads V1-V3.

Abstract: SUMMARYRight bundle branch block and ST segment elevation (RBBB-STE) in the right precordial leads have been reported as a distinct clinical and electrocardiographic syndrome in patients prone to ventricular fibrillation (VF) in the absence of structural heart disease (Brugada syndrome). The purpose of the study was to investigate the role of signal averaged electrocardiogram (SAECG) in identifying patients at high risk among asymptomatic RBBB-STE patients. Thirteen patients with the RBBB-STE ECG were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…However, the existence of conduction delay at the RVOT has been suggested in many reports. [4][5][6][11][12][13][14] In addition, several clinical studies have suggested that spontaneous episodes of VF are triggered by premature ventricular contractions originating mainly from the RVOT. 19 However, this electrical abnormality has not been shown by endocardial mapping in a routine electrophysiologic study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the existence of conduction delay at the RVOT has been suggested in many reports. [4][5][6][11][12][13][14] In addition, several clinical studies have suggested that spontaneous episodes of VF are triggered by premature ventricular contractions originating mainly from the RVOT. 19 However, this electrical abnormality has not been shown by endocardial mapping in a routine electrophysiologic study.…”
Section: Discussionmentioning
confidence: 99%
“…The positive LP that characterizes BS is defined at our institution as a root mean square voltage of the last 40 ms <20 V. 5 …”
Section: Signal-averaged Ecgmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive late potential characterizing BS is defined in our institution as the root mean square voltage of the last 40 ms <20 V. 8 The P-wave signal-averaged ECG was recorded in all 15 controls by using a P-wave triggered and bidirectionally filtered mode (MAC VU ECG unit; Marquette Co, Milwaukee, WI, USA). The FPD was calculated from the vector magnitude of the X, Y, Z leads.…”
Section: Signal-averaged Ecgmentioning
confidence: 99%
“…Arrhythmias such as premature ventricular contraction, monomorphic ventricular tachycardia, [3][4][5] polymorphic ventricular tachycardia, and ventricular fibrillation (VF) 1,2,6 and a high incidence of positive ventricular late potentials have been reported in patients with BS. [7][8][9] The discovery of associated mutations of the sodium channel gene in some patients confirmed the primary electrical nature of the disease. 10,11 If BS is a sodium channel disease, it is possible that an electrical abnormality exists not only in the ventricular myocardium but also in the atrial myocardium.…”
mentioning
confidence: 93%